Pb-207, C-13 and H-1 nuclear magnetic resonance studies of lead(IV) carboxylates in solution - Claridge, T; Nettleton, E; Moloney, M (1997)
Lead(IV) reagents are widely used for the mediation of oxidation and carbon-carbon bond-forming reactions, which are postulated to proceed by mechanisms involving ligand exchange processes at the metal centre. This paper reports multinuclear (207Pb, 13C and 1H) magnetic resonance studies on lead(IV) carboxylates containing acetate, benzoate and cinnamate ligands, either as single-ligand (PbX4) or as mixed-ligand (PbXmYn.) species. At ambient probe temperatures (ca. 300 K), averaged spectra were observed for all solution species, arising from rapid intermolecular ligand exchange. At 225 K, exchange was sufficiently slow for mixed-ligand complexes, of general formula PbX2Y2, to exhibit spectra of five distinct complexes, which were shown to correspond to PbXm1,Y4-m (m = 0-4). Analysis of the low-temperature spectra presented an overall picture of chemical shift changes throughout the complexes when ligand exchange takes place. These data provide some insight into the behaviour of these complex es in solution which help explain the observed chemistry of more elaborate lead(IV) carboxylates. © 1997 by John Wiley and Sons, Ltd.